2015
DOI: 10.1021/am507575z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Poly(tetramethylene ether)glycol and Poly(ε-caprolactone) Based Dynamic Network via Quadruple Hydrogen Bonding with Triple-Shape Effect and Self-Healing Capacity

Abstract: A novel dynamic network was successfully prepared via self-complementary quadruple hydrogen bonding through Upy-telechelic poly(tetremethylene ether) glycol (PTMEG) and four-arm star-shaped poly(ε-caprolactone) ((4)PCL) precursors. The structure and the dynamic feature were identified by FT-IR and (1)H NMR. The differential scanning calorimetry (DSC) analysis indicated that the crystalline PCL and PTMEG segments show a separated melting peak, and the aggregation of Upy dimer was also observed. The dynamic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
123
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 65 publications
(107 reference statements)
3
123
0
2
Order By: Relevance
“…Supramolecular polymers based on UPy groups have been widely investigated and materials with important characteristics such as stimuli-responsive [23], self-healing [10,11,[49][50][51][52] and temperature responsive [53,54] properties have found applications within printing [55][56][57][58], cosmetics [59,60], adhesives [61] and coatings [62]. As an example of how supramolecular associations can play an important role, for inkjet printing applications a UPy-modified polyether mixed with stabilizers, antioxidants and colourants was used in work by Jaeger et al [55].…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular polymers based on UPy groups have been widely investigated and materials with important characteristics such as stimuli-responsive [23], self-healing [10,11,[49][50][51][52] and temperature responsive [53,54] properties have found applications within printing [55][56][57][58], cosmetics [59,60], adhesives [61] and coatings [62]. As an example of how supramolecular associations can play an important role, for inkjet printing applications a UPy-modified polyether mixed with stabilizers, antioxidants and colourants was used in work by Jaeger et al [55].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Depending on the supramolecular motif, this is possible by exposure to chemicals 6 or solvents, 7 change of pH 8 or temperature, 9 irradiation with light, [9][10] application of electricity, [11][12] redox environments, 13 amongst others. The quadruple hydrogen-bonded 2-ureido- 4[1H]pyrimidinone (UPy) motif, which features a high dimerization constant and is easy to synthesize and functionalize, 7,14 has become a widely utilized building block in many supramolecular polymers, 1,7,[14][15][16][17][18][19][20][21][22] both as a linear chain extender [23][24][25] and as a cross-linker. 19,[21][22]25 Initial work on UPycontaining supramolecular polymers focused on studies in solution, before the advantages of reversible bond formation in the context of melt-processing were explored.…”
Section: Introductionmentioning
confidence: 99%
“…In TRSME, the material can recover from temporary shape to original shape through two intermediate predefined shapes. Unlike the SMPs that have much attention from researchers of the TRSME [81][82][83][84], the research progress of such effect in SMA is somehow stagnant. To the best knowledge of the authors, the only study of TRSME in SMA is reported by Tang et al [85].…”
Section: Bulk Micromachined Smamentioning
confidence: 99%